2022
DOI: 10.3390/w14162546
|View full text |Cite
|
Sign up to set email alerts
|

Land Reclamation in a Coastal Metropolis of Saudi Arabia: Environmental Sustainability Implications

Abstract: Coastal reclamation for residential, tourism, and commercial developments in the Arabian Peninsula and other global regions has dramatically increased in recent decades. This phenomenon is undoubtedly innovative and novel; however, it disrupts the natural balance of marine environments and degrades coastal and marine resources. Moreover, the long-term sustainability of such developments might be undermined by rising water levels, earthquakes, and the behavior of filling material and others. This paper analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 72 publications
0
3
0
1
Order By: Relevance
“…Dampak negatif akibat kegagalan struktur diantaranya berupa penurunan tanah (land subsidence) dan pembuburan tanah (liquifaction) yang dapat diidentifikasi potensi terjadinya melalui uji kualitas tanah (soil test) pada saat perencanaan reklamasi (Sun et al, 2018;Sachpazis, 2011). Dampak negatif reklamasi terhadap lingkungan diantaranya menghilangkan jasa lingkungan, mengubah pertumbuhan kota menjadi acak akibat tarikan pusat ekonomi baru, meningkatkan risiko banjir, mempengaruhi kesetimbangan garis pantai sekitarnya, meningkatkan intrusi air laut hingga menimbulkan kemacetan lalu lintas (AlQahtany et al, 2022;Nadzira, Ibrahima, & Mansorb, 2014).…”
Section: Motif Dan Dampak Reklamasiunclassified
“…Dampak negatif akibat kegagalan struktur diantaranya berupa penurunan tanah (land subsidence) dan pembuburan tanah (liquifaction) yang dapat diidentifikasi potensi terjadinya melalui uji kualitas tanah (soil test) pada saat perencanaan reklamasi (Sun et al, 2018;Sachpazis, 2011). Dampak negatif reklamasi terhadap lingkungan diantaranya menghilangkan jasa lingkungan, mengubah pertumbuhan kota menjadi acak akibat tarikan pusat ekonomi baru, meningkatkan risiko banjir, mempengaruhi kesetimbangan garis pantai sekitarnya, meningkatkan intrusi air laut hingga menimbulkan kemacetan lalu lintas (AlQahtany et al, 2022;Nadzira, Ibrahima, & Mansorb, 2014).…”
Section: Motif Dan Dampak Reklamasiunclassified
“…Similarly, Oman lost 14.3% (24 ha) of natural mangroves from 1996 to 2020 (Bunting et al, 2022). This was mainly due to the growth of urban development activities related to coastal infrastructure and industrial expansion (Milani, 2018;Arshad et al, 2020;Aljenaid et al, 2022;AlQahtany et al, 2022), in addition to climate change impacts (Al-Naimi et al, 2016;Almahasheer, 2018;Blanco-Sacristań et al, 2022). However, some studies reported stable to slight increases in mangrove cover over the same period in the GCC countries (Almahasheer et al, 2016;Almahasheer, 2018;Milani, 2018).…”
Section: Contribution Of Remote Sensing Studiesmentioning
confidence: 99%
“…High-resolution remote sensing data offers significant information, ease of acquisition, real-time capability, and high accuracy, making it widely applicable in various fields. The phenomenon of coastal erosion [2] , resulting from human-induced land reclamation [3,4] and other integrated factors, often occurs. Currently, extensive monitoring of such events through manual field surveys is time-consuming and labor-intensive.…”
Section: Introductionmentioning
confidence: 99%